The effect of ponicidin on CFA-induced chronic inflammatory pain and its mechanism based on network pharmacology and molecular docking - Wang, Peng; Jiang, Huiyi; Yao, Jinzhong; He, Guangting; Tao, Tao; Qin, Zaisheng (Frontiers in Medicine, 2025)
PurposeInflammation is a frequent precursor to the development of chronic pain. Ponicidin, a compound derived from traditional Chinese medicine, possesses immunomodulatory and anti-inflammatory properties. However, whether ponicidin mitigates inflammatory pain through its anti-inflammatory effects and potential target molecules remains to be further explored. In this study, we investigated the analgesic effects of ponicidin in a mouse model of Complete Freund's Adjuvant (CFA)—induced inflammatory pain and employed network pharmacology to predict the potential therapeutic targets of ponicidin for pain treatment.MethodsInitially, we established a mouse model of inflammatory pain induced by Complete Freund's Adjuvant (CFA). Following the establishment of the model, the analgesic effects of ponicidin were assessed using behavioral tests, and further validation was conducted through hematoxylin and eosin (H&E) staining, enzyme-linked immunosorbent assay (ELISA), and immunofluorescence methods. Subsequently, we analyzed the potential analgesic targets of ponicidin using network pharmacology approaches and molecular docking.ResultsIn this study, we observed that ponicidin has a significant alleviating effect on CFA-induced inflammatory pain. Our results suggest that ponicidin may alleviate inflammatory pain by reducing inflammatory responses in the spinal cord and hind paw of CFA model mice. Furthermore, we found that ponicidin can mitigate the activation of macrophages in the subcutaneous tissue of the hind paw and microglia in the dorsal horn of the spinal cord. Network pharmacology analysis suggests that ponicidin may exert its analgesic effects through a multi-target, multi-pathway mechanism. Key transcription factors such as nuclear factor NF-κB p105 subunit (NFKB1), RELA, SP1, signal transducer and activator of transcription 3 (STAT3), and repressor element 1 silencing transcription factor (REST) may be involved in the underlying mechanisms of ponicidin's analgesic action. Through molecular docking and experimental validation, we have identified toll-like receptor 4 (TLR4) and hypoxia-inducible factor 1-alpha (HIF1A) as key targets of ponicidin's analgesic effects.ConclusionsPonicidin alleviates inflammatory pain by reducing inflammatory responses in the spinal cord and hind paw of the CFA model mice. TLR4 and HIF1A may as key targets for the analgesic effects of ponicidin.